Pemanfaatan Sumber Daya Lokal Untuk Optimalisasi Budidaya Tanaman Pangan Di Pulau Nias - Agustinus Tafonao; Todermanto Lawolo; Toni Yusman Lawolo; Veniman Gulo; Yoel Melsaro Larosa; Helmin Parida Zebua (Jurnal Ilmu Pertanian dan Perikanan, 2025)
The modernization of the agricultural sector through the application of appropriate technology and eco-friendly innovations has become a key pillar in achieving advanced, independent, and sustainable agriculture. This study aims to examine the role of various technologies—such as drone-based land mapping, smart farming systems, green technology, and agricultural waste utilization—in improving agricultural efficiency and productivity in Indonesia. This review is based on 23 relevant scientific journals covering aspects of technology, farmers’ socio-economics, and agricultural policy. The results of the discussion show that the integration of modern technology, farmer group empowerment, and adaptive policy support is a crucial strategy to address current agricultural challenges, including climate change and limited resources. Therefore, collaboration between farmers, the government, and academia is essential to promote widespread and sustainable adoption of agricultural technologies.